(untitled) (Modern education and development, 2024)
Writing is one of the most essential skills in language learning, yet it remains one of the most challenging areas for secondary school students. This article aims to analyze effective strategies for improving writing skills among secondary school learners. By addressing key issues that students face, such as grammar, vocabulary, structure, and creativity, the article proposes practical approaches that teachers and learners can employ to enhance writing proficiency.